Tradisi Empat Bulanan dan Simbolisme Ikan Nilem (Osteochilus hasselti) dalam Budaya Masyarakat Banyumas, Jawa Tengah - Muh. Sulaiman Dadiono; Petrus Hary Tjahja Soedibya; Purwo Raharjo; Ariya Abdul Gani (Indo Journal of Multidisciplinary Science, 2025)
This discussion examines the tradition of the Banyumas community in the four-monthly pregnancy ritual (slametan) involving the use of nilem fish (Osteochilus hasselti) as part of the symbol and offering. The purpose of this discussion is to understand the cultural meaning, social function, and transformation of the practice in the modern era. qualitative descriptive method with a combination of literature study (desk study) and field observation, conducted in Banyumas Regency, Central Java Province. The results of the discussion show that nilem fish in the four-monthly event has a symbolic meaning of fertility, fetal health, and the safety of pregnant women. This tradition is still carried out from generation to generation, although it has undergone several adjustments to the current socio-economic context. This study concludes that preserving this kind of tradition is important in maintaining local cultural identity, as well as being a subject of study in the fields of food anthropology and health ethnography.